2019
DOI: 10.1186/s40795-019-0278-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: effect of low-FODMAP rye bread versus regular rye bread on the intestinal microbiota of irritable bowel syndrome patients: association with individual symptom variation

Abstract: Background: A low intake of Fermentable, Oligo-, Di-, Mono-saccharides and Polyols (FODMAPs) is effective in the symptom control of irritable bowel syndrome (IBS) patients but may exert negative effects on the intestinal microbiota. The microbial effects of increasing regular or non-FODMAP fibre sources are largely unknown. Furthermore, it is not known if the baseline microbiota composition is associated with individual symptom control during the consumption of different rye products in IBS patients. Our objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Flavonifractor has been previously linked to IBS, being increased in children with IBS in whom the amount of Flavonifractor was negatively associated with abdominal pain. 67 Another study reported this taxon was decreased in patients with IBS after increased rye fiber consumption, 68 but similar to the current study, there was no association to pain. Interestingly elevated levels of Flavonifractor were also found in the rectal mucosa biopsies of autistic children with gastrointestinal disorders and pain.…”
Section: Discussionsupporting
confidence: 84%
“…Flavonifractor has been previously linked to IBS, being increased in children with IBS in whom the amount of Flavonifractor was negatively associated with abdominal pain. 67 Another study reported this taxon was decreased in patients with IBS after increased rye fiber consumption, 68 but similar to the current study, there was no association to pain. Interestingly elevated levels of Flavonifractor were also found in the rectal mucosa biopsies of autistic children with gastrointestinal disorders and pain.…”
Section: Discussionsupporting
confidence: 84%
“…Part of this was thought to be due to the high interindividual variation in gut microbiota composition, as there was no separation in clustering of the microbiota composition using principal coordinates analysis based on Bray–Curtis distance between the groups (Schutte et al., 2018), and samples before and after intervention of a particular individual seemed to cluster close together. In a randomized clinical trial, the effect of low‐FODMAP (fermentable oligo‐, di, and monosaccharides, and polyols) rye bread versus regular rye bread on the intestinal microbiota of irritable bowel syndrome patients was investigated (Laatikainen et al., 2019). Compared with baseline, consumption of the low‐FODMAP rye bread decreased the abundance of Bacteroides , Flavonifractor , Holdemania , Parasutterella , and Klebsiella , whereas the regular rye bread decreased the abundance of Flavonifractor .…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%
“…Compared with baseline, consumption of the low‐FODMAP rye bread decreased the abundance of Bacteroides , Flavonifractor , Holdemania , Parasutterella , and Klebsiella , whereas the regular rye bread decreased the abundance of Flavonifractor . When comparing between the two test breads, Klebsiella was decreased after low‐FODMAP rye bread intake (Laatikainen et al., 2019).…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Of further interest is the relationship between Blautia abundance and gastrointestinal symptoms. IBS patients, whose gastrointestinal symptoms decreased with a low-FODMAP diet, had higher abundance of Blautia [ 51 ], suggesting visceral sensitivity in these individuals. In contrast, individuals with PWS exhibit a high tolerance to pain and discomfort [ 52 ].…”
Section: Main Textmentioning
confidence: 99%